2016
DOI: 10.18410/jebmh/2016/504
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Traumatic Tympanic Membrane Perforations in Relation to Aetiology and Management

Abstract: The aim of the study was to evaluate the various aetiological factors incidence and type of hearing loss, clinical presentation, treatment, prognosis and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Likewise in Singh's study conductive hearing loss was found in 50 patients (83.33%) while mild degree of hearing loss was noted in 40 patients (66.66%). 10 Our observation is also in accordance with study of Adegbiji from Nigeria, revealed that conductive hearing loss was the most common type of hearing impairment accounted for 326(61.6%), followed by sensorineural hearing loss 134(25.3%), while the common degree of hearing impairment was mild to moderate degree of hearing loss that accounted for 249(47.1%). 15 In present study spontaneous healing took place in 97 patients (85.1%), however amongst surgical procedures overlay myringoplasty was commonest (7, 6.1%) in those where perforation persisted beyond six months, which is keeping with Wani's work where overall spontaneous healing was achieved in 91.1% patients, and tympanoplasty was performed in 8(2.3%) patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Likewise in Singh's study conductive hearing loss was found in 50 patients (83.33%) while mild degree of hearing loss was noted in 40 patients (66.66%). 10 Our observation is also in accordance with study of Adegbiji from Nigeria, revealed that conductive hearing loss was the most common type of hearing impairment accounted for 326(61.6%), followed by sensorineural hearing loss 134(25.3%), while the common degree of hearing impairment was mild to moderate degree of hearing loss that accounted for 249(47.1%). 15 In present study spontaneous healing took place in 97 patients (85.1%), however amongst surgical procedures overlay myringoplasty was commonest (7, 6.1%) in those where perforation persisted beyond six months, which is keeping with Wani's work where overall spontaneous healing was achieved in 91.1% patients, and tympanoplasty was performed in 8(2.3%) patients.…”
Section: Discussionsupporting
confidence: 91%
“…8,9 In current study amongst the cause of TTMP, slap trauma was most common (70.2%, n-80), subsequently trauma due to blast was found in 17 patients (14.9%), which is keeping with results of Ahluwalia, Al-Juboori, Singh, Irfan, Rai, who also reported that TTMP was mainly due to slap trauma to the ears. 7,8,[10][11][12] However etiologic factors of this study differs from that of, Ravi, Dawood, Sannigrahi, and Al-Obiedi where traumatic tympanic perforation was predominantly caused by blast injuries while in one study road traffic accidents was main cause of tympanic membrane perforation. 3,5,13,14 We found that in majority of patients left ear was affected more (58.7%, n-67), and commonest site of perforation of membrane was anterioinferior (43.9% n-50) quadrant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation